Hierarchy in International Relations - David A. Lake (Cornell University Press, 2009)
I was compelled to write this book by the United States’s invasion of Iraq.As war edged ever closer in late 2002 and early 2003, I grew increasingly concerned that the unilateralism of President George W. Bush, and especially his insistence on preventive war despite the expressed opposition of stalwart allies, was undermining the international legitimacy of the United States. I worried that the absence of any evident plan to reconstruct the Iraqi state would create instability and disorder throughout the region and show the United States incapable of fulfilling its promises to protect and provide order to other states as well.These anxieties were rather inchoate at the time. I had difficulty expressing my concerns to those who would listen and found to my dismay that the concepts and tools of my professional discipline were of limited use. When I spoke of the dangers of undermining the international authority of the United States, I was acutely aware that this concept was alien, denied, and excluded by the theories that I taught to students and used as guides to develop my own understanding of world politics. The core assumption of the discipline of international relations is that the international system is anarchic or devoid of authority. But if the international system is anarchic, and states lack authority over one another, how could the nonexistent authority of the United States get weaker? What did it mean to say that the legitimacy of the United States was fraying or that the allies were defying Washington when commonsense definitions of these concepts were ruled out by our established theories of international relations? In working through these questions, I have come to view international politics through a new lens—one that is explained and focused in this book.Today, I see authority as a form of international power, coequal with and perhaps even more important than coercion. As a political construct, authority does not exist absent the legitimacy conferred by subordinates. By engaging in preventive war against Iraq, the United States overstepped the limits of the international authority that it had previously earned. In turn, I recognize that authority rests on an exchange of political order for legitimacy and compliance. To give up some portion of their sovereignty, subordinate states must get something in return—usually international security—that is equally if not more valuable. By failing to ensure stability in Iraq after the toppling of Saddam Hussein, the United States reneged on its end of the bargain. Rather than creating order in the region, and the world more generally, the United States exaggerated threats to justify an invasion and then, as of this writing, failed to build a new and effective state to replace the one it destroyed. Finally, I appreciate that the decision of one state to subordinate itself to another is a profound act.